Social Enterprise Dalam Perspektif Maqashid Syariah: Studi Pada PT Kampung Marketerindo Berdaya - Reva Rizki Amalia; Wahanani Mawasti (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
This study aims to reveal the social enterprise innovation implemented by PT Kampung Marketerindo Berdaya to empower rural communities with a maqashid al-syariah perspective. So far, quite a number of previous studies have discussed the theme of maqashid al-syariah. However, mostly in the perspective of Islamic law and its application in banking. This study contributes to outlining the suitability of social enterprise practices and community empowerment when viewed from the maqashid sharia principles. The research method used in 2 stages, namely online data search and in-depth interviews. Marketer village empowerment innovations are in the form of: 1) training village youth with online business technology skills, 2) building empowerment in the form of social enterprise, 3) connecting village skilled workers to urban businessmen who need their services. The results of the study show that the empowerment of the Marketer Village with the profit for benefit social enterprise model is in line with the principles of Maqashid Syariah, both in terms of orientation, implementation and the resulting benefit.